Aches and Pains’ of Filipino Migrant Workers in Malaysia: A Profile of Work-Related Musculoskeletal Disorders - Labao, Hernan C.; Erwin, M. Faller; Bacayo, May Florence D (2018)
Musculoskeletal disorders (MSDs) are alarmingly high among migrant workers in Malaysia. MSDs are the most prevalent occupational-related conditions in most parts of the world affecting function, productivity and overall health-related quality of life. Therefore, this study aims to determine the profile of Filipino migrant workers in Malaysia and their various musculoskeletal complaints. Method: This study utilized a quantitative, nonexperimental, cross-sectional research design. A total of 60 subjects were randomly selected after passing the study’s sampling criteria. The Nordic Musculoskeletal Questionnaire (NMQ) was to used to determine common MSDs affecting the various regions in the body. The Demographic Pofile Sheet was provided to gather a subject’s demographic characteristics. Results: Filipino migrant workers mostly complain of pain in the low back area (60%) and shoulder pain (60%), followed by pain in the upper back (48.3%) and neck pain (45%) in the last 12 months. Household workers accounting for 73.3% of the subjects commonly complain of pain in the hips/thighs (78.9%), while workers in the service industry commonly complain of knee pain (39.1%). Conclusions: Results imply that Filipino migrant workers have a higher prevalence of shoulder and lower back pain in the last 12 months. Household workers are more susceptible to hip/thigh pain. Interventions focusing on ergonomics policy implementation, education on posture and lifting techniques and physical function is recommended. Further studies should consider the psychological and psychosocial aspects of migrant employment, which are known risk factors for MSDs